“Evaluación de cuatro métodos de polinización controlada en dos ecotipos de piñón blanco (jatropha curcas L.) en la región San Martín” - Archentti Reátegui, Fernando (2015)
This research work entitled "Evaluation of tour methods of controlled pollination on two ecotypes of white Pinion (Jatropha curcas L.) in the region San Martín" aimed to evaluate the results of four controlled pollination methods on two ecotypes of white pinion and determine the most effective controlled pollination. Design was applied in randomized complete block 4 x 2 factorial arrangement (4 x 2 ecotypes methods) with four (4) replications and eight (8) treatments. For improvement work, four methodologies controlled po'llination (bagging, sorbet and brush) and a control treatment (natural pollination) was applied. This experiment demonstrates that managed to develop methods for improving pollination white pinion and found that the Caballococha ecotype with the implementation of the straw method obtained higher grain yield per hectare 1 146.87 grains I ha. lt was found, also, that the Caballococha ecotype obtained a greater number of fertilizad fruits (7.47 fruits) and the natural method scored higher fertilization with fruits by 10.18 pollinators like bees and wasps. For methods of fertilization and breeding improvement between ecotypes methods bagging and brush that obtained 7.34 and 6.52 respectively fruits is recommended. Keywords: ecotypes, controlled pollination, natural pollination, emasculated, fertilizad fruits.